2000
DOI: 10.1046/j.1365-2524.2000.00227.x
|View full text |Cite
|
Sign up to set email alerts
|

‘She has made me feel human again’: an evaluation of a volunteer home-based visiting project for mothers

Abstract: For analysis of respiratory system mechanics the very complex structure of the respiratory system is strongly simplified to a simple resistance-compliance-model. While for most patients this simplification seems sufficient, in patients with pulmonary disease this model is inappropriate. Additionally, to regional inhomogeneity throughout the lung, large volume accelerations due to the strongly decreased respiratory system compliance together with a mass increase of the patients' lungs, i.e. an increased respira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
70
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(80 citation statements)
references
References 17 publications
6
70
0
Order By: Relevance
“…The role of befrienders varies widely from project to project, and the characteristics of the befrienders also vary, including both volunteers and paid staff. Befriending has the potential to foster friendship, with the reciprocities entailed in this 30,31 and concomitant gains experienced by peer-befrienders. 32 For befriendees, a volunteer visit may be experienced as very different from that of a professional, perhaps without fear of institutional intervention in their family or care choices, which may be especially welcomed by older people trying to maintain their independence.…”
Section: Psychosocial Interventionsmentioning
confidence: 99%
“…The role of befrienders varies widely from project to project, and the characteristics of the befrienders also vary, including both volunteers and paid staff. Befriending has the potential to foster friendship, with the reciprocities entailed in this 30,31 and concomitant gains experienced by peer-befrienders. 32 For befriendees, a volunteer visit may be experienced as very different from that of a professional, perhaps without fear of institutional intervention in their family or care choices, which may be especially welcomed by older people trying to maintain their independence.…”
Section: Psychosocial Interventionsmentioning
confidence: 99%
“…Volunteers have been involved in bereavement support (Relf, 1998), well-woman clinics (Merrell, 2000a), hospice work (Field et al, 1997), home visitation (Taggert et al, 2000), and addiction prevention (McKnight & Pandak, 2000).…”
Section: Volunteerismmentioning
confidence: 99%
“…Donating time is formal volunteering (Jirovec & Hyduk, 1998) and so is receiving no payment besides travelling expenses (Merrell, 2000b). Volunteerism can reduce spending (Taggert et al, 2000) and is a form of social solidarity and community participation (Morehead, 1996). Volunteers are campaigners and change agents who facilitate community involvement, challenge the medical dominance (Merrell, 2000b), demystify health information and encourage people to make informed choices (Merrell, 2000a).…”
Section: Volunteerismmentioning
confidence: 99%
“…According to Taggart et al, who conducted a study of the Sutherland Family Network, a volunteer home visiting project in the Sutherland Shire, Sydney, Australia, home visitation is undergoing a revival in health and welfare systems [4]. Such programmes utilizing volunteers are just one form of home visitation and a way of breaking down social and cultural barriers between the formal health care system and the client.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that befriending others is a significant role of the neighbourhood volunteer [4,5] although other roles can include those of engaging with professionals in direct care partnerships [6], meeting nonmedical needs [7], manual work [8], and emotional support [9]. Befriending alone can be an effective way of relieving loneliness and isolation for those living in community settings, particularly if living alone, by helping them to communicate and develop social networks.…”
Section: Introductionmentioning
confidence: 99%